Gestão do Conhecimento baseado na análise de GAP de competências: Um estudo de caso do DETRAN-RN - Guimarães, Mirna Santiago (2008)
The Knowledge Management in organizations is a continuous process of learning that is given by the integration of data, information and the ability of people to use this information. The Management Skills is concerned to understand the powers of officials in the face of organizational skills (teams) and professionals (or tasks positions) want. Joints are located in the greater context of the economy of organizatio s and have the same assumption: that the possession of scarce resources, valuable and difficult to imitate gives the organization a competitive advantage. In this sense, this thesis proposes a model of knowledge management based on analysis of GAP of powers, namely the gap between the skills needed to reach the expected performance and skills already available in the organization, officials and trainees of Coordination of Registration of conductors of DETRAN-RN. Using the method of survey research could make an analysis of academic skills, techniques and emotional individual and a team of officials and trainees, identifying levels of GAP's competence in that sector of the organization and suggest a plan for training , A level of expertise for each sector of coordination, and propose a model for Knowledge Management to help the management of GAP's identified